1998
DOI: 10.1055/s-2007-978949
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Improves Weight Velocity and Height Velocity in Prepubertal Children with Cystic Fibrosis

Abstract: We undertook this study to determine if growth hormone treatment of prepubertal children with cystic fibrosis could improve their height and weight. Nine prepubertal children with cystic fibrosis were treated with human recombinant growth hormone for one year. Results obtained during this year were compared to similar measurements made for each patient for the one year prior to the treatment year. Anthropometric data including: height, height velocity, weight, weight velocity and skin fold thickness were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 18 publications
(33 reference statements)
3
22
0
Order By: Relevance
“…35,37,38 The duration of treatment with rhGH ranged from 6 months to 3 years. Ages of the patients in the studies ranged from 6 months to 13 years, [31][32][33][34][35][36]38 with the exception of 1 case report of a patient aged 18 years. 37 Doses of rhGH in the studies ranged from 0.16 to 0.35 mg/kg per week, 32,33,35,36,38 with the exception of 1 case report in which the dose was 2.2 mg/day.…”
Section: Single-arm Observational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…35,37,38 The duration of treatment with rhGH ranged from 6 months to 3 years. Ages of the patients in the studies ranged from 6 months to 13 years, [31][32][33][34][35][36]38 with the exception of 1 case report of a patient aged 18 years. 37 Doses of rhGH in the studies ranged from 0.16 to 0.35 mg/kg per week, 32,33,35,36,38 with the exception of 1 case report in which the dose was 2.2 mg/day.…”
Section: Single-arm Observational Studiesmentioning
confidence: 99%
“…31,34 Baseline measures of height and weight were inconsistently reported among the observational studies, but all patients had deficient height and weight for their age. [31][32][33][34][35][36][37][38] Data Synthesis A summary of the results for all key questions of both qualitative and quantitative synthesis and strength of evidence is listed in Table 3. Forest plots of pooled analyses are available at www.…”
Section: Single-arm Observational Studiesmentioning
confidence: 99%
“…Growth hormone treatment enhances nutrition, linear growth and weight in children with CF [38], in prepubertal children may improve height, weight, bone mineral content and lean body mass [39], and may reduce the number of hospitalizations with or without significantly changing pulmonary function, even in children receiving enteral nutritional supplementation [39,40]. Children homozygous for the Delta F508 mutation, which is associated with the most severe disease, fail to normalize growth despite improved care [41].…”
Section: Impaired Growth and Development And Impact Of Chronic Steroimentioning
confidence: 99%
“…Height and weight velocities were also used as primary efficacy measures for several recombinant human growth hormone trials, demonstrating improved growth in children with CF whose height and weight were less than or equal to the 25th percentile (40)(41)(42). In addition, the phase 3 efficacy trials of inhaled tobramycin demonstrated improved weight gain in the treatment group (43).…”
Section: Clinical Efficacy Measuresmentioning
confidence: 99%